Tracer experiments for dispersion modelling in river Douro water quality management - Duarte, António A. L. Sampaio (2000)
Parameters estimation for in situ dispersion river water behaviour characterisation, and performance evaluation of numerical models, applied to reproduce data field obtained from dye tracer experiments, were the main purposes of this research work. A monitoring program was carried out using tracer injection to assess the environmental impact of accidental pollutant discharges in an international reach of river Douro, between Castro dam (Spain) and Miranda dam (Portugal). This paper presents the methodology used in the tracer experiments, the concentration-time curves, describing dye tracer spread, the results of different simulation and their agreement with the measured data, and peak attenuation with dye spread travel time. Longitudinal dispersion coefficients values are estimated according to the river hydrodynamics.